1980
DOI: 10.1159/000212405
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Protein Synthesis during the Life Span of Male Fischer Rats

Abstract: The cell-free protein synthetic activity of the postmitochondrial supernatant isolated from whole brain of 6- to 32-month-old male Fischer F344 rats was compared. Protein synthesis decreased 56% from 6 to 32 months of age. The decrease in cell-free protein synthesis was not due to an age-related increase in RNase activity. Although monomeric ribosomes (ribosomes stripped of mRNA) isolated from the brains of older rats were less active in polyuridylic acid directed polyphenylalanine synthesis, the fidelity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…They found that each tissue has a distinct pattern of incorporation of [14C]leucine into protein as a function of age. The decrease with age in protein synthesis of rat (Breuer & Florini, 1965) and mouse (Srivastava, 1969) skeletal muscle, of rat brain (Murthy & Rappoport, 1965;Ekstrom, Liu & Richardson, 1980), and the increase in rat liver (Murthy, 1966) in in vitro systems agree with the in vivo results of Kanungo et al (1970). In contrast, Mainwaring (1969) observed a decline in the in vitro incorporation of [Wlphenylalanine into the liver of old mice, and a decline in the in vivo rate of liver protein synthesis has been observed in old Sprague-Dawley rats .…”
Section: Rationale For the Study Of Protein Metabolism During Agingsupporting
confidence: 74%
“…They found that each tissue has a distinct pattern of incorporation of [14C]leucine into protein as a function of age. The decrease with age in protein synthesis of rat (Breuer & Florini, 1965) and mouse (Srivastava, 1969) skeletal muscle, of rat brain (Murthy & Rappoport, 1965;Ekstrom, Liu & Richardson, 1980), and the increase in rat liver (Murthy, 1966) in in vitro systems agree with the in vivo results of Kanungo et al (1970). In contrast, Mainwaring (1969) observed a decline in the in vitro incorporation of [Wlphenylalanine into the liver of old mice, and a decline in the in vivo rate of liver protein synthesis has been observed in old Sprague-Dawley rats .…”
Section: Rationale For the Study Of Protein Metabolism During Agingsupporting
confidence: 74%
“…The other mechanism is decreasing content of the enzyme molecules, which manifests in late senescence (Table I). It is known that the rates of protein synthesis and turnover in several tissues, such as brain, liver, and thymus, decrease in aged animals (30)(31)(32). Therefore, we speculate that the Na + , K + -ATPase activity of SPM decreases by two mechanisms: an altered lipid microenvironment, which starts from the early stages of senescence; and a diminished enzyme content in the late stages.…”
Section: Discussionmentioning
confidence: 84%
“…Prior to this time, the experimental methods did not consider specific activity of the precursor pool (reviewed by Richardson and Birchenall-Sparks, 1983), which resulted in highly variable outcomes across studies. Using improved methodology, several groups found that levels of brain protein synthesis increase during development in the rodent, reaching maximum levels sometime during the first 6 months of age, and then decline thereafter (Dwyer et al, 1980; Ekstrom et al, 1980; Fando et al, 1980; Ingvar et al, 1985; Smith et al, 1995; but see Filion and Laughrea, 1985; reviewed by Richardson, 1981; Richardson and Birchenall-Sparks, 1983; Richardson et al, 1983). A similar pattern was observed in the white leghorn chicken (Yang et al, 1977).…”
Section: Transcription and Translation In The Aging Brainmentioning
confidence: 99%
“…A similar pattern was observed in the white leghorn chicken (Yang et al, 1977). There is some disagreement pertaining to the exact time course of the decline, with some finding a greater rate of decline in translation during adulthood (Ekstrom et al, 1980; Fando et al, 1980; Ingvar et al, 1985; Smith et al, 1995), and others finding the greatest rate of decline during senescence (Dwyer et al, 1980). Similarly, although protein synthesis decline has been observed in many other types of tissues and cells (e.g., liver, kidney, muscle), the time courses and rates of decline vary (reviewed by Webster, 1985).…”
Section: Transcription and Translation In The Aging Brainmentioning
confidence: 99%